2010
DOI: 10.1016/j.canep.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and phytosterols differentially regulate the expression of caveolin 1 and a downstream prostate cell growth-suppressor gene

Abstract: Background-The purpose of our study was to show the distinction between the apoptotic and anti-proliferative signaling of phytosterols and cholesterol enrichment in prostate cancer cell lines, mediated by the differential transcription of caveolin-1, and N-myc downstream regulated gene1 (NDRG1), a pro-apoptotic androgen-regulated tumor suppressor.Methods-PC-3 and DU145 cells were treated with sterols (cholesterol and phytosterols) for 72 h, followed by trypan blue dye exclusion measurement of necrosis and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Real-time quantitative PCR (qPCR) analysis was conducted using KOD SYBR qPCR Mix (TOYOBO) with the fluorescent dye SYBR Green and a ABI Prism 7000 (PerkinElmer Life Sciences) for detection. Primer pairs for the Bcl-xL gene PCR were synthesized according to the previous report 59 . The PCR protocol was performed as described in the instruction manual.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR (qPCR) analysis was conducted using KOD SYBR qPCR Mix (TOYOBO) with the fluorescent dye SYBR Green and a ABI Prism 7000 (PerkinElmer Life Sciences) for detection. Primer pairs for the Bcl-xL gene PCR were synthesized according to the previous report 59 . The PCR protocol was performed as described in the instruction manual.…”
Section: Methodsmentioning
confidence: 99%
“…CAV1 inhibits epidermal growth factor tyrosine kinase, extracellular signal-regulated kinase, threonine protein kinase, serine protein kinases, including Src family tyrosine kinase, protein kinase C alpha (PKCα), and H-Ras, via the CAV1 scaffolding domain [ 6 , 7 , 8 , 9 ]. Several studies attempted to develop phytochemicals with the potential of regulating CAV1 expression in various cell lines [ 10 , 11 , 12 ]. Recent reports evaluating the pathogenesis of liver fibrosis have suggested that CAV1 may play an important role in chronic liver disease [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these observations suggest that biological differences in tumorigenesis may be a factor in the course of disease among races 6. Indeed, numerous studies have characterized several genes, the expression patterns and variants7,8 of which determine the tumoral heterogeneity9 which characterizes the disparity in incidence and aggressiveness of disease found among African-American and Caucasian patients 10,11. Currently, there is a good deal of literature claiming that lifestyle factors impact the risk of prostate cancer in African- Americans.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Indeed, numerous studies have characterized several genes, the expression patterns and variants 7 , 8 of which determine the tumoral heterogeneity 9 which characterizes the disparity in incidence and aggressiveness of disease found among African-American and Caucasian patients. 10 , 11 Currently, there is a good deal of literature claiming that lifestyle factors impact the risk of prostate cancer in African- Americans. Accordingly, the wide variations in cancer incidence among populations living in different regions of the world echo the suggestion that the majority of malignant tumors are triggered by environmental factors.…”
Section: Introductionmentioning
confidence: 99%